Handboek voor de vredesbeweging : de radicaal-pacifistische stromingen - de Graaf, Johannes; Hugenholtz, J.B. Th.; Meertens, P.J.; Simons, W.J.; Bremer, H.; Buter, W.; Jong, W. (s' Gravenhage: Nijgh & Van Ditmar, 1954)
"onder redactie van J. De Graaf, J.B. Th. Hugenholtz, P.J. Meertens en W.J. Simons; met medewerking van H. Bremer, M. Buter, W. Jong Etc."